Application of fuel cells in transportation - Ziliukas, Antanas (Transport, 2004)
The development of fuel sort of vehicles assumes a wide spectrum of application in America and Europe. Safety assessment is needed for car exploitation using hydrogen fuel. Therefore this article covers the control methodology of defects adapting the science advancement for hydrogen fuel operation. To achieve this aim the damage prevention methodology of mechanic phenomena and damage modeling for hydrogen fuel cells is suggested. In the presented methodology the methods and steps of safety assessment are discussed.First Published Online: 27 Oct 2010